2016
DOI: 10.1039/c6ra16957k
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymer and organic salts in forming aqueous biphases: a platform to identify molecular interactions in aqueous medium

Abstract: An aqueous solution of a tri-block copolymer PPG–PEG–PPG has been used with two organic salts, sodium acetate and sodium citrate, to create new aqueous biphasic systems (ABS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…11−16 Scarcer are the studies evaluating the possibility of creating ABS composed of Pluronics and other polymers (e.g., dextran). 17,18 Foreseeing their future application, some authors unveiled the extraction aptitude of Pluronic-based ABS for metallic ions, 19,20 peptides/proteins, 12,13,17 and vitamins, 15 as well as their use for the extractive transformation of steroids. 21 Liu et al 22 reported the combined use of copolymers and cholinium-based ILs, focusing on the liquid−liquid equilibrium data and the impact of the copolymer nature on the ABS formation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11−16 Scarcer are the studies evaluating the possibility of creating ABS composed of Pluronics and other polymers (e.g., dextran). 17,18 Foreseeing their future application, some authors unveiled the extraction aptitude of Pluronic-based ABS for metallic ions, 19,20 peptides/proteins, 12,13,17 and vitamins, 15 as well as their use for the extractive transformation of steroids. 21 Liu et al 22 reported the combined use of copolymers and cholinium-based ILs, focusing on the liquid−liquid equilibrium data and the impact of the copolymer nature on the ABS formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of (EO) x -(PO) y -(EO) x copolymers in ABS is not new, and their combination with conventional salts to induce liquid–liquid demixing in aqueous solution is well documented. Their phase separation phenomena were systematically studied considering distinct salts and Pluronics (varying both the molecular weight and EO/PO ratios) at distinct temperatures and pH. Scarcer are the studies evaluating the possibility of creating ABS composed of Pluronics and other polymers (e.g., dextran). , Foreseeing their future application, some authors unveiled the extraction aptitude of Pluronic-based ABS for metallic ions, , peptides/proteins, ,, and vitamins, as well as their use for the extractive transformation of steroids . Liu et al reported the combined use of copolymers and cholinium-based ILs, focusing on the liquid–liquid equilibrium data and the impact of the copolymer nature on the ABS formation.…”
Section: Introductionmentioning
confidence: 99%
“…The tie-line data were fitted to Othmer-Tobias and Bancroft equations, eqs and ): where W 1 t is the mass fraction of Brij 35 in the top phase; W 2 b is the mass fraction of the salt in the bottom phase; W 3 b and W 3 t are the mass fractions of water in the bottom and the top phases, respectively. K 1 , n , k 2 , and r are the fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous biphasic systems mainly comprise water as the solvent and have low interfacial tension, providing a mild and promising biocompatible environment for the efficient extraction and purification of metal species, drugs, and organic biomolecules. Moreover lower cost, nontoxicity, and the possibility of large scale application make aqueous biphasic extraction systems handier over conventional extraction methods. ABSs are formed by mixing certain aqueous solutions of two hydrophilic polymers or a combination of a polymer with a salt or surfactant with a salt above a definite critical concentration. In recent days, ionic liquids are also involved in designing new ABSs. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation